Vaccine Containing the Three Allelic Variants of the Plasmodium vivax Circumsporozoite Antigen Induces Protection in Mice after Challenge with a Transgenic Rodent Malaria Parasite - Gimenez, Alba Marina; Lima, Luciana Chagas; Françoso, Katia Sanches; Denapoli, Priscila M. A.; Panatieri, Raquel; Bargieri, Daniel Y.; Thiberge, Jean-Michel; Andolina, Chiara; Nosten, Francois; Renia, Laurent; Nussenzweig, Ruth S.; Nussenzweig, Victor; et al. (Frontiers in Immunology, 2017)
Plasmodium vivax is the most common species that cause malaria outside of the African continent. The development of an efficacious vaccine would contribute greatly to control malaria. Recently, using bacterial and adenoviral recombinant proteins based on the P. vivax circumsporozoite protein (CSP), we demonstrated the possibility of eliciting strong antibody-mediated immune responses to each of the three allelic forms of P. vivax CSP (PvCSP). In the present study, recombinant proteins representing the PvCSP alleles (VK210, VK247, and P. vivax-like), as well as a hybrid polypeptide, named PvCSP-All epitopes, were generated. This hybrid containing the conserved C-terminus of the PvCSP and the three variant repeat domains in tandem were successfully produced in the yeast Pichia pastoris. After purification and biochemical characterization, they were used for the experimental immunization of C57BL/6 mice in a vaccine formulation containing the adjuvant Poly(I:C). Immunization with a recombinant protein expressing all three different allelic forms in fusion elicited high IgG antibody titers reacting with all three different allelic variants of PvCSP. The antibodies targeted both the C-terminal and repeat domains of PvCSP and recognized the native protein on the surface of P. vivax sporozoites. More importantly, mice that received the vaccine formulation were protected after challenge with chimeric Plasmodium berghei sporozoites expressing CSP repeats of P. vivax sporozoites (Pb/PvVK210). Our results suggest that it is possible to elicit protective immunity against one of the most common PvCSP alleles using soluble recombinant proteins expressed by P. pastoris. These recombinant proteins are promising candidates for clinical trials aiming to develop a multi-allele vaccine against P. vivax malaria.